Prognostic Implications of Heterogeneity in Intra-tumoral Immune Composition for Recurrence in Early Stage Lung Cancer - Mony, Jyothi Thyagabhavan; Schuchert, Matthew J. (Frontiers in Immunology, 2018)
Background: Studies in the past have identified selected immune cells that associate with different clinical outcomes in non-small cell lung cancer (NSCLC). However, differences suggest that heterogeneity in immune responses needs to be accounted. We asked whether distinct intra-tumoral combinations/immune-phenotype comprising of prognostic immune cell types can predict recurrence in early stage NSCLC. Objective: To evaluate the individual and combined effects of diverse intra-tumoral immune cell types in the prognosis of recurrence in early stage lung adenocarcinoma after surgical resection. Methods: We obtained NCBI GEO datasets for lung adenocarcinoma, the most prevalent histological subtype of NSCLC and re-analyzed the gene expression data of 298 patients with early stage cancer (IA/IB). CIBERSORT was used to resolve 22 immune cell types from the tumor transcriptomes. Survival analysis was carried out to assess the effect of immune cell types and genes associated with recurrence. Results: Out of the 22 cell types, a high proportion of Tregs and monocyte-macrophages in the tumors were associated with significantly increased probability of recurrence. Conversely, increased proportion of non-Treg CD4+ T cells and plasma cells were associated with a lower probability of recurrence. In concordance, the higher expression of chemokines, CCL20 that can direct migration of cells of B cell lineage and XCL1 associated with prototypical Th1 immune response, as well as immunoglobulin chains IGHV4.34 and IGLV6.57 of antibodies were associated with a significantly lower probability of recurrence. Importantly, the intra-tumoral immune phenotype comprising these four cell types varied among patients and differentially associated with recurrence depending on net levels of positive and negative prognostic factors. Despite a high level of intra-tumoral plasma cells, a concomitant high level of monocyte-macrophages reduced the freedom from recurrence from ~80% to ~50% at 80 months (p<0.05). Furthermore, stratification of the patients on the basis of a score estimated from the levels of four cell types enabled the identification of patients with significantly increased probability of recurrence (~50%) after surgery. Significance: Recurrence is the bane of treating lung cancer and the identification of prognostic immune phenotypes in patients has implications for treatment strategies, development of immunoscore and refinement of TNM staging.